Development of a cohesive zone model for three-dimensional simulation of joint debonding/delamination under mixed-mode I/II fatigue loading. Issue 3 (28th August 2014) - Pirondi, Alessandro; Giuliese, Gregorio; Moroni, Fabrizio
Abstract : Purpose: In this work, the cohesive zone model developed by some of the authors to simulate the propagation of fatigue defects in two dimensions is extended in order to simulate the propagation of defects in 3D. Design/methodology/approach: The procedure has been implemented in the finite element solver (Abaqus) by programming the appropriate software-embedded subroutines. Part of the procedure is devoted to the calculation of the rate of energy release per unit, G, necessary to know the growth of the defect. Findings: The model was tested on different joint geometries, with different load conditions (pure mode I, mode II pure, mixed mode I / II) and the results of the analysis were compared with analytical solutions or virtual crack closure technique (VCCT). Originality/value: The possibility to simulate the growth of a crack without any remeshing requirements and the relatively easy possibility to manipulate the constitutive law of the cohesive elements makes the cohesive zone model attractive also for the fatigue crack growth simulation. However, differently from VCCT, three-dimensional fatigue debonding/delamination with CZM is not yet state-of-art in finite element softwares